Ethnic and Linguistic Differences in the COVID-19 Mortality in Rural Localities in Moldova - Slav, Maxim; Ștîrba, Vitalie (Calitatea Vieții, 2025)
The COVID-19 pandemic revealed a visible discrepancy in mortality levels between countries, regions, and populations depending on their socioeconomic and demographic characteristics. Scientific literature shows the influence of individual, behavioural and institutional factors on COVID-19 outcomes, including risk of death. Additionally, state institutions seemed to have a crucial influence on COVID-19 mortality depending on their capacity to respond timely to population health challenges by reducing the risk of death and unnecessary disease sequelae. This research is conducted based on a hypothesis that people respond to the COVID-19 crisis depending on the information available in their mother tongue and their usually spoken language, which ultimately leads to a discrepancy in COVID-19 mortality between populations by characteristics of ethnolinguistic groups (ethnicity, mother tongue, and usually spoken language). Thus, by employing a linear regression model, we compared the level of COVID-19 mortality among the main ethnicities in Moldova. Our results revealed a significantly higher mortality level in the Russian-speaking population. We speculate that our results can be explained by the influence of external, often Russian-language, misinformation about COVID-19. This likely contributed to greater vaccine hesitancy, particularly regarding western-made vaccines. Additionally, higher levels of institutional mistrust among ethnic minorities in Moldova, combined with limited institutional capacity to communicate effectively with these communities, may have further reinforced this trend. The results could serve the central and local authorities in implementing targeted health policies to diminish health inequalities among populations by socioeconomic and ethnolinguistic characteristics.